Obstetric interventions and maternal morbidity among women who experience severe postpartum hemorrhage during cesarean delivery. (August 2017) - Seligman, K.; Ramachandran, B.; Hegde, P.; Riley, E.T.; El-Sayed, Y.Y.; Nelson, L.M.; Butwick, A.J.
Highlights: Outcomes after severe hemorrhage during cesarean section were examined. Methylergonovine is the most common second line uterotonic. One third of women receive red blood cell transfusions. Hysterectomy is a key intervention for severe hemorrhage during prelabor cesarean section. Abstract: Background: Compared to vaginal delivery, women undergoing cesarean delivery are at increased risk of postpartum hemorrhage. Management approaches may differ between those undergoing prelabor cesarean delivery compared to intrapartum cesarean delivery. We examined surgical interventions, blood component use, and maternal outcomes among those experiencing severe postpartum hemorrhage within the two distinct cesarean delivery cohorts. Methods: We performed secondary analyses of data from two cohorts who underwent prelabor cesarean delivery or intrapartum cesarean delivery at a tertiary obstetric center in the United States between 2002 and 2012. Severe postpartum hemorrhage was classified as an estimated blood loss ≥1500 mL or receipt of a red blood cell transfusion up to 48 h post-cesarean delivery. We examined blood component use, medical and surgical interventions and maternal outcomes. Results: The prelabor cohort comprised 269 women and the intrapartum cohort comprised 278 women. In the prelabor cohort, one third of women received red blood cells intraoperatively or postoperatively, respectively. In the intrapartum cohort, 18% women received red blood cells intraoperatively vs. 44% postoperatively ( P  <0.001). In the prelabor and intrapartum cohorts, methylergonovine was the most common second-line uterotonic (33% and 43%, respectively). Women undergoing prelabor cesarean delivery had the highest rates of morbidity, with 18% requiring hysterectomy and 16% requiring intensive care admission. Conclusion: Our findings provide a snapshot of contemporary transfusion and surgical practices for severe postpartum hemorrhage management during cesarean delivery. To determine optimal transfusion and management practices in this setting, large pragmatic studies are needed.